Targeting oncogenic protein kinase Cι for treatment of mutant KRAS LADC. (2nd January 2017) - Fields, Alan P.; Ali, Syed A.; Justilien, Verline; Murray, Nicole R.
ABSTRACT: Lung cancer is the leading cause of cancer death in the US with ∼124, 000 new cases annually, and a 5 y survival rate of ∼16%. Mutant KRAS -driven lung adenocarcinoma ( KRAS LADC) is a particularly prevalent and deadly form of lung cancer. Protein kinase Cι (PKCι) is an oncogenic effector of KRAS that activates multiple signaling pathways that stimulate transformed growth and invasion, and maintain a KRAS LADC tumor-initiating cell (TIC) phenotype. PKCι inhibitors used alone and in strategic combination show promise as new therapeutic approaches to treatment of KRAS LADC. These novel drug combinations may improve clinical management of KRAS LADC.